Gender differences in the formation of the epileptic system in male and female rats depending on the stage of the estrous cycle on the model of focal cobalt epilepsy - T. A. Voronina; S. A. Litvinova; Y. B. Filatova (LLC "Publisher OKI", 2022)
In this work, the features of the formation of the epileptic system in male and female rats, depending on the stages of the estrous cycle, were studied on the model of focal cobalt epilepsy. It was found that in male rats at the stable stage of the first stage of development of the epileptic system, Epi activity (the number and duration of discharges per minute) is most pronounced in the contralateral and ipsilateral cortex, and in female rats, the leading brain structures involved in the generation of EpA depend on the phases of the estrous cycle. In the diestrus2 phase, in females, the leading structure generating EpA, as in males, is the contralateral cortex, and in the proestrus and estrus phases, which are characterized by a high content of sex hormones, in females there is a significant predominance of EpA in the lateral hypothalamus and dorsal hippocampus.